2022
DOI: 10.1002/mats.202200066
|View full text |Cite
|
Sign up to set email alerts
|

Polyimide/Silica Nanocomposites with Enhanced Tensile Strength: Size Effects and Covalently Bonded Interface

Abstract: In this work, the tensile strength of polyimide/silica composites with the covalently bonded interface (bonded PI/SiO 2 ) is investigated by molecular dynamic simulation. It is found that the nanofiller with smaller size can bring out a larger number of hydrogen bonds and interfacial non-bond energy in the composites, resulting in higher tensile strength. As the immobilization of the PI chains in the vicinity of SiO 2 , the covalently bonded interface is found to offer a greater reinforcing effect than the unb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The optimization methods of PI/SiO 2 composite models had been introduced in detail in a previous study. 35 The optimized PI/SiO 2 composite model was shown in Figure 1c. To minimize the random error in the simulation, all the simulation results were repeated three times at least.…”
Section: Molecular Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimization methods of PI/SiO 2 composite models had been introduced in detail in a previous study. 35 The optimized PI/SiO 2 composite model was shown in Figure 1c. To minimize the random error in the simulation, all the simulation results were repeated three times at least.…”
Section: Molecular Simulationmentioning
confidence: 99%
“…Many studies have demonstrated that organic molecules can improve the interfacial strength and the mechanical properties of the composites. [35][36][37] Compared to polymer modifications with the complex preparation process, flexible and controllable silane coupling agents are favored to reinforce the load transfer efficiency in the composites. However, few studies have attempted to investigate the silane coupling agents that can elevate the ε r and mechanical properties of the composites simultaneously.…”
mentioning
confidence: 99%
“…Their calculations demonstrated that reduced local mobility above the glass transition point increased the yield stress (σ y ) and decreased the Poisson’s ratio (μ) in a glassy state. Additionally, researchers also extensively explored the mechanical properties of PI materials enhanced by nanoparticles, graphene, and carbon nanotube (CNT) , through MD methods.…”
Section: Introductionmentioning
confidence: 99%